ChatGPT as a coping mechanism: Postgraduate use under supervisory gaps in South-South Nigerian tertiary institutions - Uka Nwagbara; Daramfon Okon; Precious Ukeje (CV Rezki Media, 2026)
Background: Generative AI tools like ChatGPT are common in higher education, especially where students lack timely academic support. In many South-South Nigerian universities, gaps in postgraduate supervision may influence how students use such tools. Objectives: This study examines how postgraduate students become aware of ChatGPT, how much they use it, and why they rely on it when supervision is limited. Methods: A qualitative exploratory design was used. Twenty-one postgraduate students were purposively selected from universities in South-South Nigeria. Data were collected through online semi-structured interviews using a validated guide. Inductive thematic analysis, using Braun & Clarke’s framework, was applied to identify patterns in the data. Results: Findings show that awareness of ChatGPT is mostly informal, driven by peers, social media, and personal trial and error. Many students use ChatGPT frequently, especially during proposal writing, data analysis, and thesis development. Its use is strongly linked to delays or gaps in supervision. Conclusions: ChatGPT is widely used as a support tool and coping strategy, rather than merely a convenience. Its role reflects gaps in supervision and the need for clearer institutional guidance and training.